Blockage of apoplastic bypass-flow of water in rice roots by insoluble salt precipitates analogous to a Pfeffer cell - Ranathunge, K.; Steudle, E.; Lafitte, R. (Wiley, 2005)
Precipitates of insoluble inorganic salts were used to clog apoplastic pores in cell walls of the outer part of rice roots (OPR) in two rice cultivars (lowland cv. IR64 and upland cv. Azucena). Aerenchyma of two different root zones (20–50 and 50–100 mm from the apex) was perfused with 1 m m potassium ferrocyanide (K4[Fe(CN)6]) while the whole root segments were bathed in 0.5 m m copper sulphate (CuSO4) medium. In another experiment, salts were applied on opposite sides of the OPR. The copper‐ferrocyanide precipitation technique resembles the famous osmotic experiments of the German botanist Wilhelm Pfeffer, in which he used them with clay diaphragms. Precipitates were observed on the side where ferrocyanide was applied, suggesting that Cu2+ and SO42– were passing the barrier including the Casparian bands of the exodermis much faster than ferrocyanide. There was a patchiness in the formation of precipitates, correlated with the maturation of the exodermis. The intensity of copper ferrocyanide staining decreased along developing rice roots. No precipitates were observed in mature parts beyond 70–80 mm from the root apex, except for sites around the emergence of secondary roots, which were fairly leaky to both water and ions. Blockage of the apoplastic pores with precipitates caused a three‐ to four‐fold reduction of hydraulic conductivity of the OPR (LpOPR). The reflection coefficient of the OPR (σsOPR) increased in response to the blockage with precipitates. The osmotic versus diffusive water permeability ratios of the OPR (PfOPR/PdOPR) were around 600 for immature and 1200 for mature root segments. Treatment significantly affected the bulk rather than the diffusive water flow and caused a three‐ to five‐fold reduction of the PfOPR/PdOPR ratios. Results indicated that despite the existence of an exodermis with Casparian bands, most of the water moved around cells rather than using the cell‐to‐cell passage.